2007
DOI: 10.1128/jcm.01243-07
|View full text |Cite
|
Sign up to set email alerts
|

Revised Culture-Based System for Identification of Malassezia Species

Abstract: Forty-six strains of Malassezia spp. with atypical biochemical features were isolated from 366 fresh clinical isolates from human subjects and dogs. Isolates obtained in this study included 2 (4.7%) lipiddependent M. pachydermatis isolates; 1 (2.4%) precipitate-producing and 6 (14.6%) non-polyethoxylated castor oil (Cremophor EL)-assimilating M. furfur isolates; and 37 (34.3%) M. slooffiae isolates that were esculin hydrolyzing, 17 (15.7%) that were non-tolerant of growth at 40°C, and 2 (1.9%) that assimilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
70
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 30 publications
(31 reference statements)
3
70
0
8
Order By: Relevance
“…Samples were obtained from healthy skin (24 dogs) and from skin lesions of atopic dermatitis (42 dogs). Each sample was derived from at least 3 areas of the external ear, paw, and abdominal regions and samples were cultured using CHROMagar Malassezia medium (CHROMagarm, Paris, France) [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were obtained from healthy skin (24 dogs) and from skin lesions of atopic dermatitis (42 dogs). Each sample was derived from at least 3 areas of the external ear, paw, and abdominal regions and samples were cultured using CHROMagar Malassezia medium (CHROMagarm, Paris, France) [2].…”
mentioning
confidence: 99%
“…Samples were obtained from healthy skin (24 dogs) and from skin lesions of atopic dermatitis (42 dogs). Each sample was derived from at least 3 areas of the external ear, paw, and abdominal regions and samples were cultured using CHROMagar Malassezia medium (CHROMagarm, Paris, France) [2].Isolates of M. pachydermatis(n=182) were identified phenotypically based on morphology and on their ability to grow on medium with no lipid supplementation [1]. The isolates were divided into two groups: Group I consisted of 72 (3 strains per 1 dog) isolates collected from the healthy skin of 24 healthy dogs, and Group II consisted of 110 (2 or 3 isolates per 1 patient) isolates collected from the atopic dermatitis skin lesions of 42 dogs (25 isolates from Japan, 22 isolates from Korea and 63 isolates from Taiwan).…”
mentioning
confidence: 99%
“…The scheme used for the identification of the isolates proposed by Kaneko et al, 26 showed good results in our laboratory to identify species. All the clinical isolates showed positive catalase reaction.…”
Section: Identification Of Clinical Isolatesmentioning
confidence: 89%
“…Moreover, the new scheme proposed by Kaneko et al 26 that requires modified CHROMagar-Malassezia medium, SGA, Tween 60-Esculin agar (EA), Cremophor El agar (CrEl) and catalase reaction, was proved. The latter scheme uses the following culture media:…”
Section: Phenotypic Identificationmentioning
confidence: 99%
See 1 more Smart Citation